Hospital Responsibility for Release of Medical Information of to Claim The Insurance in Telogorejo Hospital Semarang - Suyoko suyoko; Budi Sarwo; Tjahjono Kuntjoro (Universitas Katolik Soegijapranata Semarang, 2019)
Hospitals are responsible to establish the patients’ medical information. However, in reality they should encounter conflicts with the third party who represents the patients to get the medical information, such as the insurance company. This research aims to discover about hospital’s responsibility in establishing patients’ medical information as a proof to claim the insurance and the problems that should be encountered by the hospital in carrying out the responsibility.This research was conducted in Telogorejo Hospital, Semarang. It implements juridical sociology approach with analytical description. The primary and secondary data were gathered from observation result, interview result, and questionnaires analyzed using the qualitative-descriptive method.The result shows that from legal aspect, Telogorejo Hospital has agreed to give the insurance companies which have partnership-relation the access to the patients’ medical information.Whereas for the insurance company which has no partnership-relation with the hospital, the medical information is given after getting the permission from the patients. It is also found out that the patients’ right for reimbursement claim has not yet been given at its best because the filling of the patients’ medical information has not satisfied the minimum, relevant, and adequate principals, so if it causes some disadvantages to the patients, the hospital is legally responsible following the Law of the Republic of Indonesia Article 46 Act Number 44 Year 2009 about Hospital based on the principle of Vicarius Liability. Nevertheless, there is no claim from the injured party. The criminal responsibility aspect of Telogorejo Hospital has protected the confidentiality of the medical information, so the implementation does not contradict with Article 322 of the Criminal Code of the Republic of Indonesia. From the administrative responsibility, Telogorejo Hospital can be expected to be responsible according to the Law of the Republic of Indonesia Article 29 verse 2 Act Number 44 Year 2009 about hospital because Telogorejo Hospital has not optimally implemented the fulfillment of the patients’ right for the medical information. Besides that, the government has not fully monitored and given proper guidance to the hospitals. The other findings are the internal factors which include the incomplete medical records and the external factors, such as the lack of understanding about medical information by the third party, such as the insurance company, and the regulation of medical information release also affect the hospital responsibility.